Catheter Ablation of Parahisian Premature Ventricular Complexes From the Right Sinus of Valsalva. - Ghannam, Michael; Simpson, Jamie; Al‐Sadawi, Mohamed; Deshmukh, Amrish; Liang, Jackson J.; Latchamsetty, Rakesh; Crawford, Thomas; Jongnarangsin, Krit; Oral, Hakan; Bogun, Frank (Journal of Cardiovascular Electrophysiology, 2025)
Background: Cather ablation of parahisian premature ventricular complexes (PVCs) often requires ablation in multiple cardiac chambers, including the sinuses of Valsalva (SoV). The safety and efficacy of ablation within the right SoV to target parahisian arrhythmias has not been widely reported. Objective: To report on the demographic and procedural characteristics of patients undergoing catheter ablation of PVCs who underwent ablation in the right SoV, and to examine the impact of late‐gadolinium enhanced cardiac magnetic resonance (LGE‐CMR) on procedural findings. Methods: Consecutive patients undergoing ablation of parahisian PVCs and ablation in the right SoV with preprocedural LGE‐CMR were included. Results: Eleven patients were included in the study population (11 males (100%), median age: 68 ± 7 years, median ejection fraction: 53% ± 7%, PVC burden 23% ± 13%). Intramural LGE‐CMR scar was present in all patients and involved the basal anteroseptum/outflow tract in nine patients. Ablation within the right SoV eliminated (n = 9) or suppressed (n = 2) PVCs in all patients. The successful SoV site displayed the absolute earliest presystolic activation time or matching pacemaps in only 44% and 55% of patients, respectfully. Transient heart block during right SoV ablation occurred in 1/11(9%) patients. The post procedure PVC burden decreased from 23% ± 13% to 7% ± 6%, procedural success was attained in 10/11(91%) of patients. Conclusions: Parahisian PVCs ablated from the right SoV are often intramural, may require ablation in multiple chambers, and colocalize with intramural LGE‐CMR scar. Traditional EGM markers of successful ablation sites were less frequently seen at successful site of SoV ablation, long term success was achieved in 91% of patients.